Association of serum vitamin D status with gestational diabetes mellitus and other laboratory parameters in early pregnant women - Caihong Luo; Zhiju Li; Yunya Lu; Fang Wei; Dongmei Suo; Shiyan Lan; Zhengyuan Ren; Runchang Jiang; Fang Huang; Aiyue Chen; Liejun Jiang; Huayi Huang; et al. (BMC, 2022)
Abstract Background The association between serum 25-hydroxy vitamin D (25(OH)D) status and gestational diabetes mellitus (GDM) gained attention in recent years, however the conclusion is still controversial due to many interfering factors, such as region of living, environment, lifestyle, and food supplements. Other metabolites (laboratory parameters) are also important in reflecting gestational states. This study aimed to investigate the association of serum 25(OH)D status in early pregnancy with GDM and other laboratory parameters in pregnant women. Methods A total of 1516 pregnant women whose blood glucose were normal before pregnancy in the city of Foshan in Guangdong, China were enrolled in this study. GDM was diagnosed between 24 to 28 weeks of pregnancy following the guidelines from the American Diabetes Association. Maternal serum 25(OH)D and other laboratory parameters-including hematology, coagulation, chemistry, and bone density-were measured utilizing various analytical methods in clinical laboratory at gestational weeks 11 to 14. Results The average 25(OH)D concentration was 59.1 ± 12.6 nmol/L. None of the study subjects had 25(OH)D < 25 nmol/L; 434 (28.6%) women had 25(OH)D deficiency (< 50 nmol/L), 882 women (58.2%) had 25(OH)D insufficiency (50-74 mmol/L) and 200 women (13.2%) had 25(OH)D sufficiency (≥ 75 nmol/L). There were 264 (17.4%) women diagnosed with GDM. There was not, however, an association between serum 25(OH)D in early pregnancy and GDM. Interestingly, women with more parity and high serum alkaline phosphatase levels had higher serum 25(OH)D levels. There was a possible positive association between serum 25(OH)D and pre-albumin, and a possible negative association between serum 25(OH)D, creatinine, and thrombin time. This study did not find an association between serum 25(OH)D and bone density. Conclusions There were no associations between maternal serum 25(OH)D concentration in early pregnancy and the risk of GDM or bone density. There were, however, correlations between serum 25(OH)D and parity, seasoning at sampling, serum alkaline phosphatase, creatinine, pre-albumin, and coagulation factor thrombin time, which need further study to explain their pathophysiology and clinical significance.